2022
DOI: 10.3126/kumj.v20i2.50565
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Study of Distal Radius Parameters in Patients Visiting Tertiary Care Hospital

Abstract: Background The important morphological parameters of distal radius namely palmar tilt, radial inclination, radial height and ulnar variance are consequential in the evaluation and management of the distal radius fracture, distal radius plate design and kinesiology. Correction of these parameters in anatomical alignment is important to restore the normal biomechanics of the wrist joint. Objective To ascertain the distal radius parameters in the patients attending tertiary care hospital with regard to gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Jongmuenwai et al (2021) confirmed the validity of RDEW as a sex discriminator for the Thai population with an accuracy of (89.5%). The effectiveness of RH for sex differentiation was assessed by Shrestha et al (2022) and Nalbant et al (2022) who studied 125 patients' wrist radiographs, they discovered that males had significantly higher RH mean values than females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jongmuenwai et al (2021) confirmed the validity of RDEW as a sex discriminator for the Thai population with an accuracy of (89.5%). The effectiveness of RH for sex differentiation was assessed by Shrestha et al (2022) and Nalbant et al (2022) who studied 125 patients' wrist radiographs, they discovered that males had significantly higher RH mean values than females.…”
Section: Discussionmentioning
confidence: 99%
“…Tested dimensions: 1) Two distal radial dimensions: the radial distal end width (RDEW) which is the greatest distance between the most medial and lateral points on the distal epiphysis of the radius (Jongmuenwai et al, 2021). The radial height (RH) defined as the distance between the horizontal line at the level of the lunate fossa, which is perpendicular to the radius' axis, and the horizontal line at the level of the radial styloid process, which is also perpendicular to the radius' axis (Shrestha et al, 2022). 2) Two distal ulnar dimensions: the ulnar distal end width (UDEW) defined as the largest ulnar width at its distal end (Monum et al, 2021).…”
mentioning
confidence: 99%
“…Various literature from hospital based study report a prevalence of diabetic retinopathy ranging from 19% to as high as 78%. 10,19,20,21 The global prevalence of DR was reported to be 34.6%. 22 Our study contradicts the findings of other reports where prevalence of DR was higher in hospital based studies which is attributed to the diabetic patients reporting to the retina department owing to visual complains.…”
Section: Discussionmentioning
confidence: 99%